What Lies Beneath: Preservation, reconstruction & reuse at Uppåkra archaeological site - Nesset Mattsson, Oskar (My University, 2025)
Next to a barn on the Scanian countryside, beneath the wheat-fields around the village of Uppåkra, lies the remains of an ancient Scandinavian power-centre. In the 2000s an impressive temple was unearthed, currently a large hall is being excavated. The rest of the settlement lies untouched, still buried in the soil. Since the inception of the conservation-field in the mid-1800s, the discipline has battled with a central question: Should we restore objects to its former glory, or preserve heritage in its present state, to display the passage of time? The answer either lands at: restoration, preservation, or somewhere in between. The thesis explores this spectrum of views on conservation, using the design of an archaeological centre at Uppåkra as a testbed for three approaches: Restoration through the reconstruction of a temple, preservation through protection of excavated remains, and the mix of these through the transformation of an old barn into a museum for found artefacts. The design departs from collecting, mapping, and representing the local archaeology. Together with research on similar typologies and conservation approaches. Keywords: Archaeology, Preservation, Conservation, Restoration, Adaptive Reuse, The thesis hinges around the span between abstraction and realism in reconstruction practices, exemplified by the abstraction of Venturi, Scott Brown’s “Ghost House” reconstruction of Franklin Court in Philadelphia, USA (1976), and the realism of Jan Gezelius’ reconstruction of Eketorps Fornborg on Öland (1984). While Venturi & Scott Brown’s project renders the massing as an “abstract” framework to reflect a lack of source material, Gezelius does the opposite, creating a “realistic” interpretation, filling knowledge-gaps with educated guesses. The thesis illustrates how the history of Uppåkra can be communicated beyond the tools of a conventional museum. By erecting an excavation-shelter that showcases the archaeological process, engaging visitors in conservation work in a transformed barn and enabling them to imagine past structures through an abstract reconstruction. Unlike previous proposals for the site, the design leaves the area largely undisturbed, enabling future excavations. By reusing existing structures and carefully placing new ones on top of past excavations. It suggests a new direction for the tradition of archaeological centres in Sweden.
Keywords: Archaeology, Preservation, Conservation, Restoration, Adaptive Reuse